Direct Csp2−H difluoromethylation of heterocycle by K2S2O8. (5th November 2021) - Dai, Peng; Jiao, Jian; Wang, Qingqing; Yu, Xiang; Teng, Peng; Zhu, Yuchuan; Gu, Yu-Cheng; Zhang, Wei-Hua
Abstract: We reveal here a novel and efficient transition-metal-free C(sp 2 )–H oxidative difluoromethylation of heterocycle. It uses stable and nontoxic NaSO2 CF2 H as difluoromethyl source and potassium persulfate as oxidant without the need for metal catalyst. Significantly, the reaction affords difluoromethyl heterocycles in moderate to good yields with a broad substrate tolerance. Graphical abstract: In this work, an efficient method for the synthesis of difluoromethylation-containing heterocycles was developed from different heterocycles and NaSO2 CF2 H by potassium persulfate. Image 1